ISSUES OF CULTURAL DIVERSITIES IN DISNEYâ€™S ANIMATED MOVIES (Reflective Essay) - Falasifatul Falah (Proyeksi: Jurnal Psikologi, 2006)
The movie â€œindustryâ€ nowadays is â€œmore sensitive to issues of culture and gender than it once wasâ€, however many pictures â€œstill perpetuate common misconception aboutâ€ cultural diversities. â€œSuch oversimplified and inaccurate portrayals can profoundly affect how [people] perceive [each other] and how [people] value [themselves]â€ (http://www.media-awareness.ca/english/parents/ movies/concerns/stereotyping_movies.cfm., undated, no page).It was Walt Disney, the person who created many famous classical stories in the 1940s and 1950s, such as Beauty and the Beast, Cinderella, Pinocio, Snow White, The Little Mermaid and Sleeping Beauty. In fact, Disneyâ€™s animated movies based on those classic stories are still popular at the moment, particularly among children around the world (Radio Suara Amerika, 2002, on line).It cannot be ignored that the viewers who are watching classic animation movies, such as Disneyâ€™s, are still â€œgetting stereotypical messagesâ€ at the moment (Mifflin, 1999, p.E.8). â€œAnimated [pictures] have their share of stereotypes, because they are familiar and easily understoodÂ  (http://www.media-awareness.ca/english/parents/movies/concerns/stereotyping_movies.cfm., undated, no page). However, it seemed that new versions of Disneyâ€™s animated movies have tried to improve the use of stereotypes (Durbin, 1998, p.2.13).In this essay, I would like to analyse some Disneyâ€™s animated movies as the particular media genre which I chose to see how they reflect cultural diversities, such as gender and race.